Absceso apical agudo y factores asociados en pacientes durante la pandemia de covid-19 en un centro de salud de Acapulco, México. - Juárez-Medel, Carlos Alberto (2024)
Objective: To estimate the prevalence of acute apical abscess and identify associated factors in patients of a health center from Acapulco, Mexico. Material and methods: Epidemiological study that collected clinical records of patients during the period of october 2021. Sociodemographic and housing information was collected, as well as personal pathological and non-pathological history and a record of the diagnosis of the periapical lesion based on its clinical characteristics issued by the operator on duty. Through multivariate analysis, a factor associated with acute apical abscess was identified with the odds ratio and its 95% confidence interval as estimators of the strength of association with CIETmap statistical software. Results: The 37% (32/87) of patients were diagnosed with the infection. In terms of gender, females were the most affected with a proportion of 56% (18/32). The most common cause was caries with 72% (23/32). The right upper second premolar was the most affected tooth with 25% (8/32). One associated factor was identified, age 36 to 62 years (ORa=3.54; CI95%a=1.27 -16.62). Conclusion: The morbidity rate of the infection was moderate, and it is a common pathology in stomatological emergency consultations, so it is important for the professional in charge of the area to manage it clinically. It will be important to implement oral health education strategies aimed at different age groups to raise awareness of the cariogenic process and its consequences.